Pengaruh Pengalaman Prakerin, Kompetensi Keahlian dan Motivasi Berprestasi Terhadap Employability Skills Peserta Didik di SMK - Ady Isnan (Contextual Natural Science Education Journal, 2026)
This study aims to discover the influence between independent variables and dependent variable, namely prakerin experience (X1), skill competence (X2), achievement motivation (X3) and employability skills (Y). The research method is quantitative research with ex post facto type. Population of this research were students of grade XII TKJ study program at SMK in Makassar City with the total of 195 students. Based on the results of the study, it can be concluded that: (1) prakerin experience, skill competence, achievement motivation and employability skills of students SMK in Makassar City is included into good category; (2) There is a significant influence and positive between prakerin experience, skill competence, and achievement motivation toward employability skills.